Collection management to reduce delinquency in financial institutions in Peru. - Victor Hugo Puican Rodríguez, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on the production of scientific papers related to the study of collection management by Peruvian financial institutions with the purpose of reducing delinquency levels. This study was carried out taking into account the documents registered in the Scopus database where research papers published in high impact journals are consigned. The search was detailed by means of different parameters, achieving the identification of a total of 106 researches that meet the requirements of the present papers. These were subjected to a mixed bibliometric and bibliographic analysis to identify the main characteristics in the volume of production, and the opinion of different authors on the aforementioned topic.